Z dziejów internowanych Polaków w Związku Sowieckim: Łagier nr 270 w Borowiczach - Rogut, Dariusz (Acta Universitatis Lodziensis. Folia Historica, 2001)
After the Soviet troops’ entrance into the former Eastern territories of Poland, the members of the Polish independence conspiracy were touched by mass repressions. The same process started on different regions of so called „Lublin Poland”. The Poles were placed in prisons and camps. They were deported far inside the Soviet Union after the research led by the NKVD officers. One of the largest concentrations of the interned Home Army (Armia Krajowa) soldiers was placed in Labours’ Group No 270 in Borowicze (region Novogrod). Almost 6000 of the Poles stayed there in the years of 1944-1949. The highest number of interned lived there between 1944 and 1946 - 4893 persons. High mortality (almost 13% in 1945) was caused by low food ration, exhausting work (10-12 hours per day), lack of suitable sanitary-higicnic conditions and basic medicines. The physical and psychological health of interned persons was devastated. They were told to work in coal mines, industry factories and field-works. The Soviet authorities lowered simultaneously the quantity of food, did not secure suitable winter and working clothes and prohibited the correspondence with families of interned persons. The Labours in Borowicze are said to have one of the worst existence conditions, where about 600 of Home Army soldiers died. Most of Polish left the labour in 1946. The next ones that came in 1947 from another places. They were released in the years of 1947-1949.